PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN PADA TANI KUMPA RAYA DI DESA MANUNGGAL DAYA - Sudarso; Luthman, Awang Yacoub; Hendra (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
The Role of Farmer Groups in increasing income for Kumpa Raya Farmers in Manunggal Daya Village. The Government of Kutai Kartanegara Regency formed a joint farmer group which aims to provide additional knowledge on renewal of systems in agriculture in order to increase the income of the people of Kutai Kartanegara Regency, especially in Manunggal Daya Village. In addition to providing additional knowledge to participants so that they can understand the process of group growth, group development is to improve group capabilities and the importance of combined farmer groups as business actors in implementing agribusiness. The purpose of this study was to determine the role of the Kumpa Raya farmer group in increasing the income of farmers in Manunggal Daya Village, in addition to knowing the role of farmer groups from an economic point of view in increasing the income of farmers in Manunggal Daya Village. The Kumpa Raya farmer group consists of 26 members, 3 of whom are administrators of the farmer group and the remaining 23 people are members of the farmer group, making a total of 26 people. From the results of the research it was found that the role of farmer groups is indeed very important in addition to being able to increase income or the economy of the community, farmer groups also act as a forum for deliberations, a place to maintain and develop knowledge, skills and mutual cooperation in farming among its members (production units). For this reason, the Kumpa Raya farmer group is very beneficial for the people of Manunggal Daya Village.